MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN METODE DEMONSTRASI DI SD NEGERI 019 PANDAU JAYA KECAMATAN SIAK HULU - Suryani Suryani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is based on the low learning result of mathematics. This study aims to improve student learningoutcomes class I.A SD Negeri 019 Pandau Jaya Kecamatan Siak Hulu.. This research uses classroom actionresearch (PTK) with two cycles by using demontration method. Based on the result of the research, the students'absorption in Mathematics lessen significantly: Pratindakan replication is 62,00 (enough); in cycle I is 67,40(enough); and the result of cycle II is 72.20 (enough). The mastery of individual and classical learning increases;initial data 13 students 52.00% (unfinished); in cycle I is 20 students and 80.00% (unfinished); and in cycle II is 24students and 96.00% (complete). Thus it can be concluded that, the implementation of demonstration methodsmanaged to improve learning outcomes Mathematics class I.A SD Negeri 019 Pandau Jaya Kecamatan Siak Hulu.